Problems Faced by Bachelor-Level Students in Learning English Vocabulary - Bhandari, Bhim Lal (Curriculum Development Journal, 2023)
English language proficiency depends on the vocabulary that students have access to. One of the most important aspects of language acquisition is mastery of vocabulary. Learners with a limited vocabulary are academically poor in several courses relating to language skills, linguistics, literature, and translation. The purpose of this research is to explore vocabulary learning issues faced by bachelor-level students studying compulsory English. The data consists of the responses of four student participants purposefully selected from two constituent campuses of TU in Rupandehi, Nepal. A phenomenological qualitative research method is employed for the study. It uses semi-structured interviews and questionnaires, as research tools to collect the data from the participants. The study’s findings show that pupils struggle with spelling, pronouncing words, using words appropriately, and discovering meaning. This study may contribute to identifying challenges that pupils have and enhance their knowledge of vocabulary acquisition.